Le théâtre d'Argentomagus (Saint-Marcel, Indre) - Dumasy, Françoise (Documents d'archéologie française, 2000)
Although not one of the largest theatres from the Gallo-Roman period, nor one of the most richly decorated, the theatre at Argentomagus is the only one in France to have been thoroughly excavated, restored and now published Its long history has been marked by frequent building alterations which have made it one of the finest examples of the Gallo-Roman theatre type, the original modest wooden-tiered structure, built in the mid first-century, was reconstructed in circa 180 A.D., only to he demolished at the end of the Roman period. In a particularly evocative manner, this edifice bears witness to the inventiveness of its architects, to the efforts of prominent citizens to Romanise their surroundings and to the local population's taste for stage performances.